Cardamom (Elettaria cardamomum) and Sappan Wood (Caesalpinia sappan L.) Proportion Effect on the Antioxidant Activity of "Wedang Kapusecang" - Maghfiroh, Khoirin; Mighfar, Shochibul (Journal of Natural Sciences and Learning, 2023)
This research explores the impact of varying proportions of cardamom and sappan wood on the antioxidant activity of Wedang Kapusecang, a heated beverage inspired by the traditional Imogiri drink "Wedang Uwuh." Using a factorial Randomized Block Design (RBD) with two factors, the study examines two levels of cardamom (0.5g and 1g) as the first factor and three levels of sappan wood (2g, 5g, and 8g) as the second factor, resulting in six treatment combinations, each duplicated twice. Data analysis employs ANOVA with 1% and 5% confidence intervals, followed by the BNT test (5%) if significant effects are detected. The study includes evaluations of antioxidant activity using the DPPH test and organoleptic aspects such as taste, aroma, and color. The research findings indicate that the most potent antioxidant activity is observed in treatment K2S3 (1g cardamom and 3g sappan wood), with an IC50 parameter of 55,604 ppm, signifying robust antioxidant properties. Organoleptic results identify treatment K2S2 (1g cardamom and 2g sappan wood) as the optimal choice, with moderately liked taste (2.76), moderately liked aroma (2.88), and liked color (3.68). Considering the effectiveness index, treatment K2S2 remains superior, exhibiting an average IC50 antioxidant activity value of 55,604 ppm (strong), with moderately liked taste and aroma ratings, along with a liked color rating.